Stratigraphic and tectonic characterization of the Peñas Coloradas Formation, and its relation with the deposits of the Chota formation in the Chota Basin of northern Ecuador - Reinoso Almeida, María Dolores (2021)
The Chota Basin is located in Ecuador, in the province of Imbabura; it represents the northernmost basin of the Interandean Depression in Ecuador. This basin is one of the most relevant for studying the evolution of the Neogene geology in this part of the country and dates from approximately 6 Ma. The importance of this type of basin is that the stratigraphy and the structures that are exposed record a lot of information about the processes that created the Cordillera Occidental and the Cordillera Real that border it. The focus of this work is the breccia deposits of the Peñas Coloradas Formation and its relation with the Chota Fm. The Peñas Coloradas Fm breccia deposits are composed mainly of conglomerates, sandstone, and breccia deposits that have not been described in detail previously. The deposits that underlie the Peñas Coloradas Fm correspond to the Chota Formation, consisting of tilted and overturned sandstone layers, siltstone, and shales that are significantly deformed. There are few previous studies in this basin, Tibaldi A. et al. (1992), Egüez, A. et al. (1994), Barragán et al. (1996), and Winkler et al. (2005). Still, the interpretations of different aspects of the basin are incongruent between them. Among the main differences is the age of the basin, the processes that lead to the origin of the basin (i.e., inverted extensional basin vs. foreland setting), and the stratigraphic sequence of the basin (the Peñas Coloradas Fm is placed either at the base or the middle of the basin stratigraphy). This study consists of describing the stratigraphy and deformation of two of the principal formations described previously by Barragan et al. (1996) and Winkler et al. (2005): the Chota and the Peñas Coloradas Fms. It is necessary to detail the stratigraphic relation between them. We make stratigraphic and structural observations that allow us to create local stratigraphic columns, cross-sections, and do the structural analysis, to understand better the stratigraphy and structural interpretations of the deposits of these units. As a result, we create a geologic map of the study area, where subdivide the Peñas Coloradas Fm into four new members: Canales Colorados Mbr, Brillosas Mbr, Tabulares Mbr, and Volcanicas Mbr. Additionally, the deformation and stratigraphy analysis allow us to conclude that the Chota Fm is older than the Peñas Coloradas Fm. Based on the field observations, we propose two models for the evolution of the Chota Basin during the deposition of the studied formations.